Prevalence of inversions in introns 1 and 22 of the factor VIII gene and inhibitors in patients from southern Brazil - Maria Cristina S. M. Corrêa; Euripides Ferreira; Marcelo T. A. Veiga; Eliane Bandinelli; Clévia Rosset
ABSTRACT Objectives: The development of antibodies (inhibitors) against exogenous factors is the main complication in the treatment of hemophilia. Both genetic and non-genetic factors are related to inhibitor development. Among the genetic factors, the type of mutation that caused the disease is one of the most important. The objectives of the present study were to establish the prevalence of inversions in introns 1 and 22 of the factor VIII gene in patients with severe hemophilia A, correlating these with inhibitor development, and to compare the results with data from the literature. Method: Unrelated severe hemophilia A patients were analyzed for the presence of inversions in intron 1 (n = 77) and intron 22 (n = 39) by polymerase chain reaction (PCR). Detection of the inhibitor was performed by the mixing test and its quantification was performed by the Bethesda method. Results: The prevalence of inversions in introns 1 and 22 was 2.6% and 41%, respectively. No patient with inversions in intron 1 had inhibitors, whereas 26.3% of patients with inversions in intron 22 developed inhibitors. Conclusion: Due to the small number of patients with inversions in intron 1, it was not possible to perform a statistical test for the correlation with risk of inhibitor development. Inversions in intron 22 of the factor VIII gene were not associated with an increased risk of inhibitor development in the analyzed samples (p = 1).